Owner-manager emotions and strategic responses of small family businesses to the COVID-19 pandemic - Christofi, Michael; Hadjielias, Elias; Mahto, Raj V.; Tarba, Shlomo; Dhir, Amandeep (My University, 2023)
COVID-19 pandemic, a consensus crisis that has had a profound effect on societies and economies globally, compelled family businesses to respond strategically in order to remain afloat. We examine the role of their owner-managers’ emotions in the strategic response to the COVID-19 pandemic, drawing on 38 in-depth interviews with owner-managers of small family businesses in Cyprus. Our findings reveal that owner-managers have experienced mainly negative emotions during the pandemic, including higher levels of stress, insecurity, fear, and doubt. By reflecting on these emotions, owner-managers can activate affective mechanisms and apply a stewardship logic to respond strategically. We contribute to the family business literature by conceptualizing key processes at the intersection between owner-manager emotions and strategic responses to the COVID-19 pandemic. By focusing on individual (that is, owner-manager) emotional processes and stewardship attitudes, our study provides a microfoundational explanation of strategic responses during external crises and offers both theoretical and practical implications.
Keywords: emotions; Family business; owner-manager; stewardship; strategic response